Chinese classical decoction Wuwei Xiaodu Drink alleviates gout arthritis by suppressing NLRP3-Mediated inflammation - Lin, Na; Dai, Qiaoding; Zhang, Yan; Xu, Liping (Frontiers in Pharmacology, 2024)
Background: Wuwei Xiaodu Drink (WWXDD), a classical decoction of traditional Chinese medicine, has been clinically used for the treatment of gout in China for many years. This study aimed to demonstrate the efficacy of WWXDD in treating gout flares and elucidate its underlying therapeutic mechanism. Methods: A randomized control trial was conducted to compare the effectiveness of WWXDD with low-dose colchicine in gout arthritis. The primary outcome was the clinical response rate on the 7th day, and joint syndrome score and serological tests were secondary outcome measures and were compared in the two groups on the 1st and 7th day. Then we used a network pharmacology approach to investigate the possible mechanism of WWXDD in treating gout, and the effects of WWXDD on the MSU-induced rat model were observed. Results: In the clinical trial, a total of 78 participants completed the study, and the results demonstrated comparable clinical complete response rates, joint symptom scores, and serological test outcomes between the two groups on the 7th day. Network pharmacology analysis identified 51 core genes that target gout and WWXDD interactions. Notably, strong significant correlations were observed with inflammation cytokine genes and metabolism-related genes. Furthermore, it was found that WWXDD reduced gene expression levels of inflammation cytokines including IL-1β, TNF, and IL-18 in an MSU-induced rat model while increasing IL-10 expression. Additionally, WWXDD decreased insulin gene expression in this model. Moreover, WWXDD exhibited a reduction in both gene and protein expressions associated with the NLRP3-mediated inflammatory pathway in inflamed joints of rats. Conclusion: The results of the present study suggested the anti-inflammatory effects of WWXDD in the treatment of gouty arthritis, partially through inhibiting NLRP3 inflammasome activation. Clinical Trial Registration:ClinicalTrials.gov, identifier ChiCTR2100047807.